Kesiapan Nelayan Tradisional Kali Adem, Muara Angke Jakarta Dalam Memanfaatkan Sistem Informasi Nelayan Pintar - Proboningtias, Diah; Riyanto, Riyanto (Jurnal Kebijakan Ekonomi, 2015)
Ministry of Marine Affairs and Fisheries (KKP) has made Smart Fishermen Information System (SINP), with application called Smart Fishermen (nelpin) on smartphone with Android system. This study aims to identify readiness in using SINP of traditional fishermen in Kali Adem Muara Angke Jakarta. The result of this study shows that readiness index of traditional fishermen in Kali Adem Muara Angke Jakarta in using SINP is 4.15 of 6. This means that traditional fishermen in Kali Adem Jakarta are ready to use SINP, but with conditional guidance The result of policy factors perform as a policy recommendations through give away cheap internet quota package to the fisherman, and an intensive training about how to using nelpin application.